Islamic social bank: an adaptation of Islamic banking? - Shifa Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Islamic banking is an experiment of the viability of Islamic economy with the aim to fulfil the socioeconomic justice that balances the material and social aspects of finance. However, the current practice of Islamic banking has yet to address the moral issues in promoting a balance between social and economic justice. Consequently, some scholars suggested that it is timely to learn from the experience of social banking model; that is an articulation of a sustainable and CSR oriented banking model in fulfilling the developmental needs of Muslim societies. Therefore, the purpose of this study is to introduce the idea of Islamic social banking based on the aspiration of Islamic moral economy. This paper will also discuss the social and sustainable features of social banking from an Islamic view which importantly will lead to social and economic development. The implication of the study is to fulfil the developmental needs of the Muslims in alleviating poverty and uplifting the social status by introducing a social bank which is Shari’ah compliance.